2007
DOI: 10.1177/0363546506296042
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Comparison of Anterior Cruciate Ligament Reconstructions with Hamstring Tendon and Patellar Tendon Autograft

Abstract: It is possible to obtain excellent results with both HT and PT autografts. We recommend HT reconstructions to our patients because of decreased harvest-site symptoms and radiographic osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
267
2
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 577 publications
(293 citation statements)
references
References 35 publications
(40 reference statements)
16
267
2
8
Order By: Relevance
“…4,18 Moreover, among the athletes who return to their preinjury sport levels, ACL reinjury occurs in 3% to 19% of ACL-reconstructed knees, and 5% to 24% of athletes sustain a contralateral ACL injury. 21,31 The authors of a recent review reported that, although the great majority (nearly 90%) of athletes obtained what was considered normal or near-normal strength values (greater than or equal to 85% to 90% of muscle strength capacity in their injured leg compared to their noninjured leg), the rate of return to sport was low. 5 This suggests that muscle strength tests commonly used as criteria T T STUDY DESIGN: Descriptive, prospective, longitudinal single-cohort study.…”
mentioning
confidence: 99%
“…4,18 Moreover, among the athletes who return to their preinjury sport levels, ACL reinjury occurs in 3% to 19% of ACL-reconstructed knees, and 5% to 24% of athletes sustain a contralateral ACL injury. 21,31 The authors of a recent review reported that, although the great majority (nearly 90%) of athletes obtained what was considered normal or near-normal strength values (greater than or equal to 85% to 90% of muscle strength capacity in their injured leg compared to their noninjured leg), the rate of return to sport was low. 5 This suggests that muscle strength tests commonly used as criteria T T STUDY DESIGN: Descriptive, prospective, longitudinal single-cohort study.…”
mentioning
confidence: 99%
“…The two most common autografts are from either the ipsilateral ST and gracilis or patellar tendon (Aune et al, 2001;Gobbi & Francisco, 2006;Paterno et al, 2010;Pinczewski et al, 2002;Pinczewski et al, 2007). Patellar tendon grafts have been the most popular surgical choice, though hamstring tendon grafts have recently become more common (Ejerhed et al, 2003).…”
Section: Acl Reconstructionmentioning
confidence: 99%
“…ACL injuries in athletes are immediately debilitating and typically require ACL reconstruction (ACLR) surgery. This procedure usually involves one of two autogenous grafts harvested from either the ipsilateral semitendinosus (ST) and gracilis or the patellar tendon (Ardern, Webster, Taylor, & Feller, 2010;Aune, Holm, Risberg, Jensen, & Steen, 2001;Gobbi & Francisco, 2006;Paterno et al, 2010;Pinczewski, Deehan, Salmon, Russell, & Clingeleffer, 2002;Pinczewski et al, 2007). Given the reduced risk of developing anterior knee pain after hamstring grafts (Ejerhed, Kartus, Sernert, Kohler, & Karlsson, 2003), the vast majority of ACLRs in elite Australian sport involve the ST tendon (Aglietti, Buzzi, Zaccherotti, & De Biase, 1994;Ejerhed et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations